Secular Stagnation and Income Distribution Dynamics. (June 2020) - Kiefer, David; Mendieta-Muñoz, Ivan; Rada, Codrina; von Arnim, Rudiger
This paper contributes to the literature on secular stagnation by estimating a measure of potential output growth for the post-war US economy derived from a novel model specification that allows for the cyclical interactions between income distribution, represented by the trajectory of the labor share of income, and economic activity, as measured by capacity utilization. The results obtained show that potential output growth exhibits a gradual decline that predates the Great Recession and follows the downward trajectory of the labor share of income, thus suggesting the existence of an important long-run relationship between income distribution and output growth in the United States.